The emergence of the academic candidate: evaluation as textual dramaturgy - Hamann, Julian; Serrano-Velarde, Kathia (Valuation Studies, 2023)
Our contribution sheds light on the dramaturgies of evaluation that precede candidate selection in academic organizations. The dramaturgies unfold across committee meetings, reviews, and reports that funnel the pool of candidates into a shortlist of prospective members. Because they are prolonged and not all stages involve copresence, the continuity and consistency of evaluative processes is a central dramaturgical problem. It highlights the constitutive role of written documents for the continuity and consistency of organizational evaluation processes. We marshal evidence from a comparative study on academic candidacy in two organizational settings: grantmakers, who select candidates for funding, and universities, who select candidates for professorships. Drawing on archived records produced in the context of research grant applications and professorial recruitments between 1950 and 2000, we distinguish two regimes of textual agency throughout the processes of evaluation: documents structure the process of candidate selection throughout dramaturgical stages, and they act as relays that transfer assessments of human actors across dramaturgical stages and time. In addition, by focusing on organizational access and showing how organizations make people before even hiring them, we draw attention to the emergence of a highly scripted dramatic figure in academic life: the candidate.